1997
DOI: 10.1046/j.1365-3059.1997.d01-83.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of component number on Rhynchosporium secalis infection and yield in mixtures of winter barley cultivars

Abstract: Mixtures of winter barley cultivars containing up to six components were grown over three years with and without fungicide treatment. Yield increases were recorded for mixtures compared with the mean of their monoculture components and there was a significant trend towards greater benefit from increased number of components. These benefits were partially attributable to a corresponding increase in control of Rhynchosporium secalis as component number increased. The potential for exploitation of mixtures in cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
6
50
0
Order By: Relevance
“…Futhermore, we confirmed that greater mixture complexity improved mixture efficiency, e.g. three to five components were more efficient for disease reduction and yield increase than two-component mixtures (Gacek et al, 1996;Newton et al, 1997).…”
Section: Discussionsupporting
confidence: 72%
“…Futhermore, we confirmed that greater mixture complexity improved mixture efficiency, e.g. three to five components were more efficient for disease reduction and yield increase than two-component mixtures (Gacek et al, 1996;Newton et al, 1997).…”
Section: Discussionsupporting
confidence: 72%
“…In the field, splash-dispersed pathogens often provide smaller host-diversity effects than do wind-dispersed pathogens (1,12,25,31,37,44,46,52,53), most likely due to the steeper dispersal gradients of splash-dispersed pathogens (19). Wind-dispersed pathogens may produce a large host-diversity effect for reduced disease because propagules tend to be more evenly mixed throughout host plants.…”
Section: Autoinfectionmentioning
confidence: 99%
“…In a two-component mixture in wheat, Jackson and Wennig 9 noted the taller of the two cultivars to contribute a greater proportion of heads. Mixtures, particularly as component number increases, generally yield higher that the component mean, even in the absence of disease 12 . However, if the most competitive component is not high yielding, the mixture performance will be adversely affected.…”
Section: Although Smith and Simpsonmentioning
confidence: 99%